Motions and Songs to Improve Basic Literacy through Animation Videos - Diana Putri Amalia. M; Elindra Yetti; Tjipto Sumadi (Jurnal Pendidikan Usia Dini, 2022)
The government incurs huge costs because of low literacy rates, which are associated with higher crime rates, poor health, and higher welfare costs, therefore the stimulation of basic literacy from an early age is important. This study aims to examine the effectiveness of animated motion learning media and songs that are interesting, innovative, and effective for improving basic literacy aspects of early childhood. This mixed-method design with the research and development stages of the ADDIE model was tested for the effectiveness of the media through a paired sample test. The research was divided into three stages, starting from needs analysis, product development, and product evaluation, involving 11 respondents in the effectiveness test. The data collection technique was carried out using a basic literacy instrument grid questionnaire, for child development, while for the feasibility of the media or products being developed it was also through a questionnaire from experts. Data were analyzed qualitatively and quantitatively. The results of the study show that there is a significant increase in basic literacy values through learning media. The findings of the integration of quantitative and qualitative data form the basis for preparing the final product to revise and complement the deficiencies of movement and song-learning media. Keywords: basic literacy, animation media, motion, and song, early childhood References: Abidin, Y. (2015). Multiliteracy Learning An Answer to the Challenges of 21st Century Education in the Indonesian Context [Pembelajaran Multiliterasi Sebuah Jawaban atas Tantangan Pendidikan Abad Ke -21 dalam Konteks Keindonesiaan (D. Sumayyah, Ed.)]. PT Refika Aditama. Bedard, C., Bremer, E., & Cairney, J. (2020). Evaluation of the Move 2 Learn program, a community-based movement and pre-literacy intervention for young children. Physical Education and Sport Pedagogy, 25(1), 101–117. https://doi.org/10.1080/17408989.2019.1690645 Bers, M. U. (2018). Coding, playgrounds, and literacy in early childhood education: The development of KIBO robotics and ScratchJr. 2018 IEEE Global Engineering Education Conference (EDUCON), 2094–2102. Bhadra, A., Brown, J., Ke, H., Liu, C., Shin, E., Wang, X., & Kobsa, A. (2016). ABC3D - Using an Augmented Reality Mobile Game to Enhance Literacy in Early Childhood. 0–3. Dodge, D. T., Colker, L. J., & Heroman, C. (2002). Creative Curriculum for Presschool (Fourth Edi). Cataloging in Publication. Edwards, L. C. (2013). Music and Movement A way of Life for the Young Child (Seventh Ed). Pearson Education, Inc. Fadillah, M., Filasofa, L. M. K., Wantini, Akbar, E., & Fauziyah, S. (2014). Early Childhood Education Edutainment (Creating Interesting, Creative, and Fun Learning) [Edutaintment Pendidikan Anak Usia Dini (Menciptakan Pembelajaran Menarik, Kreatif, dan Menyenangkan)]. Kencana Prenadamedia Group. Fajriyah, L. (2018). Development of Emergent Literacy in Early Childhood [Pengembangan Literasi Emergen Pada Anak Usia Dini]. Proceedings of the ICECRS, 1(3). https://doi.org/10.21070/picecrs.v1i3.1394 Fox, J. E., & Schirrmacher, R. (2015). Art & Creative Development for Young Children (Eighth Edi). Cengage Learning. Graber, K. C., & Woods, A. M. (2013). Physical Education & Activity for Elementary Classroom Teachers. Mc Graw Hill. Heydon, R., McKee, L., & O’Neill, S. (2018). Singing our song: The affordances of singing in an intergenerational, multimodal literacy programme. Literacy, 52(3), 128–136. https://doi.org/10.1111/lit.12135 Jamaris, M. (2017). Multiple Intelligences Measurement [Pengukuran Kecerdasan Jamak]. Ghalia Indonesia. Juniasih, I. (2015). Increasing Movement Creativity Through Story-Based Educational Dance Activities (Tarita) PAUD PPs Jakarta State University [Peningkatan Kreativitas Gerak Melalui Kegiatan Tari Pendikan Berbasis Cerita ( Tarita ) PAUD PPs Universitas Negeri Jakarta]. Jurnal Pendidikan Usia Dini, 9(2), 319–342. Karaca, N. H. (2017). Implementation Of Thinking Creatively in Action And Movement Test For Turkish Children Eylem Ve Harekette Yaratıcı Düşünme Testi’nin Türk Çocuklarına Uyarlanması. Mehmet Akif Ersoy Üniversitesi Eğitim Fakültesi Dergisi, 0(42), 240. https://doi.org/10.21764/efd.26968 Lastari, A. A. I. I. A., Gading, I. K., & Antara, P. A. (2016). Audiovisual to Improve Kinesthetic Intelligence in Group B Children [Audiovisual Untuk Meningkatkan Kecerdasan Kinestetik Pada Anak Kelompok B]. Journal Pendidikan Anak Usia Dini Universitas Pendidikan Ganesha, 4(2). Mariati, P., & Asmara, B. (2017). Development of Innovative Learning Models of Motion and Thematic Songs for Integrated Early Childhood Post Teachers (Ppt) in the City of Surabaya [Pengembangan Model Pembelajaran Inovatif Gerak Dan Lagu Tematik Bagi Guru Pos Paud Terpadu ( Ppt ) Di Kota Surabaya]. Jurnal Anak Usia Dini Dan Pendidikan Anak Usia Dini, 3, 9–20. Mayesky, M. (2002). Creative activities for Young Children (7 Th Editi). Delmar Thomson Learning. Nash, K., Howard, J., Miller, E., Boutte, G., Johnson, G., & Reid, L. (2018). Critical racial literacy in homes, schools, and communities: Propositions for early childhood contexts. Contemporary Issues in Early Childhood, 19(3), 256–273. https://doi.org/10.1177/1463949117717293 Pogue, B. J. (2018). Using Music and Movement to Enhance Cognitive Development Using Music and Movement to Enhance Cognitive Development. Education. Priansa, D. J. (2017). Development of Innovative, Creative, and Achievement Learning Strategies & Models in Understanding Students [Pengembangan Strategi & Model Pembelajaran Inovatif, Kreatif, dan Prestatif dalam Memahami Peserta Didik]. Pustaka Setia. Rakhmawati, N. I. S. (2016). The Use of Playing Strategy through Movements and Songs in Dealing Hypersensitivity Problems for Early Childhood. Proceedings of International Research Clinic & Scientific Publications of Educational Technology, 2013, 6–29. Rasi, P., Vuojärvi, H., & Ruokamo, H. (2019). Media Literacy for All Ages. Journal of Media Literacy Education, 11(2), 1–19. https://doi.org/10.23860/jmle-2019-11-2-1 Respati, R., Nur, L., & Rahman, T. (2018). Motion and Song as a Model for Stimulating the Development of Kinesthetic Intelligence in Early Children [Gerak Dan Lagu Sebagai Model Stimulasi Pengembangan Kecerdasan Kinestetik Anak Usia Dini]. Jurnal Pendidikan Usia Dini, Vol.12(No.2), 321–330. https://doi.org/10.21009/JPUD.122.13 Rowe, M. L., Kirby, A. L., Dahbi, M., & Luk, G. (2022). Promoting Language and Literacy Skills through Music in Early Childhood Classrooms. The Reading Teacher, n/a(n/a). https://doi.org/10.1002/trtr.2155 Ruhaena, L. (2015). Multisensory Models: Solutions to Stimulate Literacy in Preschool Children [Model Multisensori: Solusi Stimulasi Literasi Anak Prasekolah]. Jurnal Psikologi, 42(1), 47–60. Safitri, N., & Agustinus. (2017). Stimulation Dance Creations Art on Gross Motor Development Children Aged. Indonesian Journal of Early Childhood Education Studies, 6(1). https://doi.org/10.15294/ijeces.v6i1.15785 Tomblin, J. B., Oleson, J., Ambrose, S. E., Walker, E. A., & Moeller, M. P. (2018). Early Literacy Predictors and Second-Grade Outcomes in Children Who Are Hard of Hearing. Child Development, 91(1), e179–e197. https://doi.org/10.1111/cdev.13158 Tomblin, J. B., Oleson, J., Ambrose, S. E., Walker, E. A., & Moeller, M. P. (2020). Early Literacy Predictors and Second-Grade Outcomes in Children Who Are Hard of Hearing. Child Development, 91(1), e179–e197. https://doi.org/10.1111/cdev.13158 Trost, W. J., Labbé, C., & Grandjean, D. (2017). Rhythmic entrainment as a musical affect induction mechanism. Neuropsychologia, 96, 96–110. https://doi.org/10.1016/j.neuropsychologia.2017.01.004 Widhianawati, N. (2011). The Effect of Movement and Song Learning in Improving Musical Intelligence and Kinesthetic Intelligence in Early Children [Pengaruh Pembelajaran Gerak dan Lagu dalam Meningkatkan Kecerdasan Musikal dan Kecerdasan Kinestetik Anak Usia Dini]. Jurnal Upi Edu, 2, 220–228. Yetti, E., & Muanivah, H. (2017). Improved Intelligence Kinesthetic Children Ages 5-6 Years through Activities of Motion and Song. 1, 16–20. Yetti, E., Syafnita, T., & Siti Syarah, E. (2019). The Effect of Motion and Song on Children`s Speaking Ability. 178(ICoIE 2018), 429–433. https://doi.org/10.2991/icoie-18.2019.92